1890 Okla. Stat. 496, ch. 25, art. 47, § 7 - (:unkn) unknown (My University, 1890)
It shall be unlawful for any person, except a peace officer, to carry into any church or religious assembly, any school room or other place where persons are assembled for public worship, for amusement, or for educational or scientific purposes, or into any circus, show or public exhibition of any kind, or into any ball room, or to any party or social gathering, or to any election, or to any place where intoxicating liquors are sold, or to any political convention, or to any other public assembly, any of the weapons designated in sections one and two of this article.
Keywords: CARRY - CERTAIN PUBLIC PLACES